2016
DOI: 10.18240/ijo.2016.07.09
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of rhegmatogenous retinal detachment associated with choroidal detachment in Chinese patients

Abstract: For CD in RRD, related factors include BCVA, IOP, lens status, refractive error, extent of retinal detachment, number of holes, and macular hole. Larger extent of retinal detachment, high myopia, and low IOP are significant and independent risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…2. Larger radius of the hole and more holes correlate with the higher myopia, which is in accordance with the investigation results that the most common macular change in highly myopic eyes is macular holes(micron scale) [25][26][27][28][29][30] , according to this model, the hole in the eye causes myopia but not myopia causes the hole.…”
Section: Verification Of This Modelsupporting
confidence: 91%
“…2. Larger radius of the hole and more holes correlate with the higher myopia, which is in accordance with the investigation results that the most common macular change in highly myopic eyes is macular holes(micron scale) [25][26][27][28][29][30] , according to this model, the hole in the eye causes myopia but not myopia causes the hole.…”
Section: Verification Of This Modelsupporting
confidence: 91%
“…The procedure chosen depends on patients’ preoperative characteristics and surgeons’ preferences [ 4 ]. Previous reports focusing on RRD progression found that prolonged preoperative waiting time is related to the development of macular-off RRD [ 5 ], irreversible macular damage [ 6 8 ], proliferative vitreoretinopathy (PVR) progression [ 9 ], and development of choroidal detachment (CD) [ 10 ]. In addition, previous studies have shown that during national meetings or holiday-time, reduced staffing is often associated with adverse patient outcomes, changes in treatment patterns, and care delays in acute cardiovascular conditions [ 1 , 11 , 12 ] and RRD patients [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports focusing on RD progression find that prolonged presurgery waiting time is related to the development of macular-off RD [ 12 ], irreversible macular damage [ 20 22 ], PVR progression [ 23 ], and development of CD [ 24 ]. We chose PVR progression, RD’s progression, and CD’s development as the signs for RD progression.…”
Section: Discussionmentioning
confidence: 99%